The effectiveness of “objective” imputation and its application to the solution of traditional and actual cases - Corcoy Bidasolo, Mirentxu (2015)
Given the traditional views that demonstrate causation in criminal facts, the renowned authoress of this article discusses a new approach to achieve this goal: the theory of objective imputation.How is this theory implemented in real-life cases? What normative standards guide this theory? Is it effective to solve criminal conflicts? These are some of the questions the authoress looks up to answer through her argumentation and herdemonstration of case studies.